2009
DOI: 10.1523/jneurosci.5531-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor GluN2B (GluRε2/NR2B) Subunit Is Crucial for Channel Function, Postsynaptic Macromolecular Organization, and Actin Cytoskeleton at Hippocampal CA3 Synapses

Abstract: GluN2B (GluR2/NR2B) subunit is involved in synapse development, synaptic plasticity, and cognitive function. However, its roles in synaptic expression and function of NMDA receptors (NMDARs) in the brain remain mostly unknown because of the neonatal lethality of global knock-out mice. To address this, we generated conditional knock-out mice, in which GluN2B was ablated exclusively in hippocampal CA3 pyramidal cells. By immunohistochemistry, GluN2B disappeared and GluN1 (GluR1/NR1) was moderately reduced, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 103 publications
(130 reference statements)
10
107
0
2
Order By: Relevance
“…In contrast, the C terminus of NR2B is sufficient to induce normal synapse formation. NR2B knockout mice exhibit a reduction in globular actin and in the density of dendritic spines (30), consistent with a role for NR2B in the organization of postsynaptic macromolecular complexes and spine formation. The important difference between the C termini of NR2 subunits seems to be the ability to interact with CaMKII.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In contrast, the C terminus of NR2B is sufficient to induce normal synapse formation. NR2B knockout mice exhibit a reduction in globular actin and in the density of dendritic spines (30), consistent with a role for NR2B in the organization of postsynaptic macromolecular complexes and spine formation. The important difference between the C termini of NR2 subunits seems to be the ability to interact with CaMKII.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to the ionotropic function of NMDARs, it has been proposed that NMDARs play a structural role in synaptic and spine stabilization (10,30). Our results show that the C terminus of NR2 subunits confers a different role to each subunit in the process of synapse formation and stabilization.…”
Section: Discussionmentioning
confidence: 68%
“…However, not just deletion but also the overexpression of NR2A in forebrain regions has been shown to cause behavioral abnormalities, such as selective impairments in social recognition that spared instrumental extinction (Jacobs and Tsien 2014). Conversely, NR2B overexpression in forebrain areas improved social recognition and recall, whereas selective deletion of NR2B in CA3 impaired LTP, which has been suggested to be an electrophysiological correlate of memory processes (Akashi et al 2009;Jacobs and Tsien 2012). Such complex cognitive responses might be due to existence of both binary (NR1/NR2A and NR1/NR2B) and tertiary (NR1/NR2A/NR2B) complexes and perhaps the overall ratio of NR2A:2B receptor subtypes affected could also contribute towards the behavioral outcomes in a given test condition Chazot and Stephenson 1997;Hawkins et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selective KO of 2B in hippocampal CA3 pyramidal cells virtually eliminated NMDAmediated currents at CA3 synapses (29). These results imply that the 2B NMDAR subunit expressed during early development might regulate the expression of other NMDAR subunits in the postsynaptic membrane.…”
Section: Discussionmentioning
confidence: 76%
“…These results suggest that 2B is crucially involved in the synapse elimination seen under control conditions. To confirm the 2B dependence of the CS synapse elimination, we next prepared the same slice cultures using 2b Some studies have shown that there are no functional NMDAR channels in 2b −/− cells in the hippocampus (20,29). If NMDARs were eliminated from all neurons in 2b −/− mutants, we would be unable to use these mice to study the specific involvement of 2B in synapse elimination.…”
Section: Resultsmentioning
confidence: 99%